Pengenalan Tajwid Sejak Dini Melalui Metode Baghdadi Di TPA Al-Ikhwan Desa Karanghaur Kabupaten Bekasi - Eka, Eka Maulidia; Abdul Muis; Ainur Rofieq (JCSE: Journal of Community Service and Empowerment, 2023)
Introduction to Qur'an using the Baghdadi method which is held with the aim of increasing knowledge about the rules and ways of reading the Qur'an according to the science of tajwid. This service activity was carried out by the village at the TPA Al-Ikhawan Karanghaur village. In carrying out this activity there are several stages, namely: Introduction to hijaiyah letters, introduction to vowels, introduction to cursive letters, introduction to Makhorijul letters, and finally practice reading in juz 'amma. This service activity was attended by 27 students at TPA Al-Ikhwan Karanghaur village. The results of this activity increased the ability of Al-Ikhwan village students to read and write the Qur'an. Before the debriefing activities took place, students were not fully able to distinguish hijaiyah letters, both in spelling and in writing. Students who have received the provision of students are able to understand the origins of the letters they read, so that reading the Qur'an becomes easier and more comprehensive. This can be seen in the implementation of the Pre Test, the children were still in the good category, 9 people, 5 enough, and 13 people less. After carrying out learning activities using the Baghdadi method, the understanding of makharijul letters and tajwid rules shows that 56% of children are already in the good category, meaning that they can achieve a good understanding of reading the Qur'an which is maximized. Although as much as 37% is still in the sufficient category, some children are proficient and considered qualified to read the Qur'an with tartil. So that children are expected to be able to be consistent in learning the science of recitation and makharijul letters and always stick to the Qur'an.